A prehospital approach to intravenous fluid therapy in patients with sepsis. (2nd October 2022) - Costello, Barry; Sinclair, Neil
Abstract : Sepsis is a life-threatening, acute condition that can lead to septic shock and haemodynamic instability; it can be fatal if not treated. It is usually a complication of a viral, bacterial and fungal infection. Patients may have severe chest, kidney and abdominal infections. Hypovolaemia is common in patients with sepsis and may lead to a poorer outcome, and early fluid expansion is often the first step in treating these patients, in line with the Sepsis Six guidance. Paramedics are often the first practitioners to attend these patients so are well placed to provide live-saving fluid resuscitation. This article focuses on intravenous fluid therapy in the prehospital setting for critically ill patients with sepsis, including considerations regarding a need for early fluid resuscitation and the choice and administration of fluid, as well as monitoring and assessing the patient response to this.